National Library of Medicine Disaster Information Management Research Center: Establishment and growth, 2008–2010 () - Love, Cynthia B. (2013)
In 2008, the National Library of Medicine (NLM) established the Disaster Information Management Research Center (DIMRC). Prior to 2008, NLM had a long history of involvement in providing health information for disaster management. Aware of this legacy and moved by the catastrophic aftermath of Hurricane Katrina, the NLM long range plan (Charting a Course for the 21st Century: NLM’s Long Range Plan 2006–2016) called for creation of a center to show “a strong commitment to disaster remediation and to provide a platform for demonstrating how libraries and librarians can be part of the solution to this national problem”. NLM was urged to “ensure continuous access to health information and effective use of libraries and librarians when disasters occur”. In response to this charge, NLM has undertaken substantial efforts to ensure that medical libraries have plans for the continuity of their operations, librarians are trained to understand their roles in preparedness and response, online disaster health information resources are available for many audiences and in multiple formats, and research is conducted on tools to enhance the exchange of critical information during and following disasters. This paper documents the history, goals, initiatives, accomplishments and future plans of the Center.